AGW615 - Advanced Business Statistics - February 2000 - PPP, Pusat Pengajian Pengurusan (2000)
UNIVERSITI SAINS MALAYSIA MASTER OF BUSINESS ADMINISTRATION Second Semester Examination Academic Session 1999/2000 February 2000 AGW615 Advanced Business Statistics Time: [ 3 hours] INSTRUCTION: